Identification of Sorafenib as a Treatment for Type 1 Diabetes - Zeng, Qin; Song, Jianfeng; Wang, Dandan; Sun, Xiaoxiao; Xiao, Yalun; Zhang, Haowei; Xiao, Yang; Zhou, Zhiguang; Deng, Tuo (Frontiers in Immunology, 2022)
Th1 cell activation is considered a key mediator of the pathogenesis of type 1 diabetes. Targeting IL-12-induced Th1 cell differentiation seems to be an effective way to block the development of type 1 diabetes. However, given the critical function of Th1 in the immune system, the potential side effects hinder the application of anti-Th1 therapy in the treatment of type 1 diabetes. To identify safe anti-Th1 treatment(s), we screened the FDA-approved tyrosine kinase inhibitor (TKI) drug library using an IL-12-induced Th1 differentiation cell model. We found that among the TKIs with little effect on T cell viability, sorafenib is the top contender for the inhibition of Th1 differentiation. Treatment of NOD mice with sorafenib significantly impeded the development of type 1 diabetes and ameliorated insulitis, which coincided with a specifically decreased accumulation of Th1 cell population in the pancreas but not in peripheral immune organs. Mechanistically, sorafenib indirectly inhibited janus kinase 2 (JAK2) activity and blocked IL-12-induced phosphorylations of JAK2 and signal transducer and activator of transcription 4 (STAT4). Since sorafenib is classified as an FDA-approved drug, it serves as a preliminary lead point for additional experimentation and may be a promising therapy for type 1 diabetes in humans.